Testing and modeling of a traditional timber mortise and tenon joint - Feio, A. O. (2014)
The structural safety and behaviour of traditional timber structures depends significantly on the performance of their connections. The behaviour of a traditional mortise and tenon timber joint is addressed using physical testing of full-scale specimens. New chestnut wood and old chestnut wood obtained from structural elements belonging to ancient buildings is used. In addition, the performance of different semi and non-destructive techniques for assessing global strength is also evaluated. For this purpose, ultrasonic testing, micro-drilling and surface penetration are considered, and the possibility of their application is discussed based on the application of simple linear regression models. Finally, nonlinear finite element analysis is used to better understand the behaviour observed in the full-scale experiments, in terms of failure mode and ultimate load. The results show that the ultrasonic pulse velocity through the joint provides a reasonable estimate for the effective- ness of the assembly between the rafter and brace and novel linear regressions are proposed. The failure mechanism and load–displacement diagrams observed in the experiments are well captured by the proposed non-linear finite element analysis, and the parameters that affect mostly the ultimate load of the timber joint are the compressive strength of wood perpendicular to the grain and the normal stiffness of the interface elements representing the contact between rafter and brace.